An Introduction to Computer Studies - Kalicharan, Noel (Cambridge : Cambridge University Press, 1988)
This book is intended for people encountering computer studies for the first time. It gives full coverage of the core and optional material from many examination syllabuses and is particularly relevant to students taking the CXC Information Technology, Cambridge O-level or International GCSE examinations
Keywords: Computer Scineces; 11030 -- computer sciences; computer sciences; Electronic data processing